URGENSI PENETAPAN ALUR LAUT KEPULAUAN INDONESIA (ALKI) IV MENURUT UNITED NATIONS CONVENTION ON THE LAW OF THE SEA (UNCLOS) 1982: THE URGENCY OF DETERMINING INDONESIAN ARCHIPELAGIC SEA LANES PASSAGE (IASLP) IV ACCORDING TO THE UNITED UNITED NATIONS CONVENTION ON THE LAW OF THE SEA (UNCLOS) 1982 - Sekartaji, Annisa; Supartono, Sugeng (Fakultas Hukum Universitas Trisakti, 2025)
Abstract Indonesia is an archipelagic country that can determine its Archipelagic Sea Route according to UNCLOS 1982. Therefore, Indonesia already has 3 (three) Indonesian Archipelagic Sea Routes (ALKI) from North to South. However, many sea user countries argue that Indonesia should establish ALKI IV from West to East. The problem is whether it is urgent, according to UNCLOS 1982, for Indonesia to establish ALKI IV and what efforts and strategies have been made by Indonesia to establish ALKI IV. By using various research methods, the results of this study bring the conclusion that the sea between the islands of Indonesia becomes open the same as before the 1957 Djuanda Declaration and before the formation of the conception of the archipelago state listed in UNCLOS 1982 if the establishment of ALKI IV. Indonesia feels free to open ALKI IV if the existence of 3 ALKIs can still accommodate the right to cross the archipelagic sea flow. Then, the draft strategy for guarding ALKI in 2022 is known to have been made by the Directorate of Strategy of Bakamla. Furthermore, Indonesia's efforts in determining ALKI IV so far are surveys that connect ALKI I with ALKI II. If Indonesia wants to make ALKI IV, all aspects must be considered. However, if Indonesia does not want to make ALKI IV, it must determine steps supporting this argument..